Tonically Active α5GABAA Receptors Reduce Motoneuron Excitability and Decrease the Monosynaptic Reflex - Canto-Bustos, Martha; Loeza-Alcocer, Emanuel; Cuellar, Carlos A.; Osuna, Paulina; Elias-Viñas, David; Granados-Soto, Vinicio; Manjarrez, Elías; Felix, Ricardo; Delgado-Lezama, Rodolfo (Frontiers in Cellular Neuroscience, 2017)
Motoneurons, the final common path of the central nervous system, are under a complex control of its excitability in order to precisely translate the interneuronal pattern of activity into skeletal muscle contraction and relaxation. To fulfill this relevant function, motoneurons are provided with a vast repertoire of receptors and channels, including the extrasynaptic GABAA receptors which have been poorly investigated. Here, we show that extrasynaptic α5 subunit-containing GABAA receptors (α5GABAAR) co-localize with choline acetyltransferase (ChAT) suggesting that these receptors are expressed in motoneurons. In these cells, α5GABAA receptors may be activated by ambient GABA, producing a tonic shunt that reduces motoneurons’ membrane resistance and affects their action potential firing properties. In addition, α5GABAA receptors shunted the synaptic excitatory inputs depressing the monosynaptic reflex induced by activation of primary afferents. Therefore, our results suggest that α5GABAA receptors may play a relevant physiological role in motor control.